2013
DOI: 10.1063/1.4801025
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal atoms pathways on rutile TiO2 (110) surface: Distribution of Ti3+ states and evidence of enhanced peripheral charge accumulation

Abstract: Coarsening (i.e., ripening) of single-atom-high, metal homoepitaxial islands provides a useful window on the mechanism and kinetics of mass transport at metal surfaces. This article focuses on this type of coarsening on the surfaces of coinage metals (Cu, Ag, Au), both clean and with an adsorbed chalcogen (O, S) present. For the clean surfaces, three aspects are summarized: (1) the balance between the two major mechanisms-Ostwald ripening (the most commonly anticipated mechanism) and Smoluchowski ripening-and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 130 publications
14
48
1
Order By: Relevance
“…We build a (3 × 2) surface supercell (three unit cells in the [001] direction and two in the [11¯0] direction), where the lattice constants of the unit cell are 2a and c along [11¯0] and [001] directions, respectively. The a = 4.57 Å and c = 2.94 Å are relaxed lattice constants of bulk TiO 2 . Spin‐polarized first‐principles calculations are performed by using Vienna ab initio simulation package (VASP) within the framework of DFT .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We build a (3 × 2) surface supercell (three unit cells in the [001] direction and two in the [11¯0] direction), where the lattice constants of the unit cell are 2a and c along [11¯0] and [001] directions, respectively. The a = 4.57 Å and c = 2.94 Å are relaxed lattice constants of bulk TiO 2 . Spin‐polarized first‐principles calculations are performed by using Vienna ab initio simulation package (VASP) within the framework of DFT .…”
Section: Methodsmentioning
confidence: 99%
“…With increasing exposure of the surface to the H source, an oxygen vacancy (O V ) is likely to form on the bridging site. Previous study has shown that O V can also donate excess electrons where the excess electron mainly distributes at the surface Ti 5c atom . Nevertheless, the built‐in potential owing to the surface dipole is basically the same as the direct adsorption of H atom.…”
mentioning
confidence: 97%
“…[69,70] On the other hand, the recent results of density functional theory (DFT) calculations performed by Cai et al suggest that the defect states have a wide distribution in TiO2. [71] The situation for the investigation of the electronic structure induced by Ha is similar to that of Obvac. A H atom on Ob gives electrons to TiO2 with local distortion.…”
Section: Electronic Structures Of Defectsmentioning
confidence: 96%
“…The molecules were suggested to adsorb on the Ti 5 c 4+ ions. These kinds of Ti 4+ ions are normally presented on the surface of TiO 2 (rutile and anatase crystalline structures), which may interact with the oxygen [23]- [27].…”
Section: Introductionmentioning
confidence: 99%